Revisiting Biological Nitrogen Fixation Dynamics in Soybeans - Ciampitti, Ignacio A.; de Borja Reis, André Froes; Córdova, S. Carolina; Castellano, Michael J.; Archontoulis, Sotirios V.; Correndo, Adrian A.; Antunes De Almeida, Luiz Felipe; Moro Rosso, Luiz H. (Frontiers in Plant Science, 2021)
Biological nitrogen (N) fixation is the most relevant process in soybeans (Glycine max L.) to satisfying plant N demand and sustaining seed protein formation. Past studies describing N fixation for field-grown soybeans mainly focused on a single point time measurement (mainly towards the end of the season) and on the partial N budget (fixed-N minus seed N removal) overlooking the seasonal pattern of this process. Therefore, this study synthesized field datasets involving multiple temporal measurements during the crop growing season with the goal of characterizing N fixation dynamics using both fixed-N (kg ha-1) and N derived from atmosphere [Ndfa (%)] to define: i) time to maximum rate of N fixation (β2), ii) time to maximum Ndfa (α2) and iii) the cumulative fixed-N. The main outcomes of this study are that 1) maximum rate of N fixation was around the beginning of pod formation (R3 stage), 2) time to maximum Ndfa (%) was after full pod formation (R4), and 3) cumulative fixation was positively associated with seasonal vapor-pressure deficit (VPD) and growth cycle length but negatively with soil clay content, and 4) time to maximum N fixation rate (β2) was positively impacted by season length, and negatively by high temperatures during vegetative growth (but positively for VPD, during the same period). Overall, variation in the timing of maximum rate of N fixation occurred within a much narrower range of growth stages (R3) than the timing of maximum Ndfa (%), which varied broadly from flowering (R1) to seed filing (R5-6) depending on the evaluated studies. From a phenotyping standpoint, N fixation determinations after R4 growth stage would most likely permit capturing both maximum fixed-N rate and maximum Ndfa (%). Further investigations more closely screening the interplay between N fixation with soil-plant-environment factors should be pursued.